97PCommunity-driven development of a modified progression-free survival ratio for precision oncology trials. (7th November 2019) - Mock, A; Heilig, C E; Kreutzfeldt, S; Hübschmann, D; Heining, C; Schröck, E; Brors, B; Stenzinger, A; Jäger, D; Schlenk, R F; Glimm, H; Fröhling, S; et al.
Abstract: Background: The success of a cancer therapy in an individual patient can be estimated by calculating the progression-free survival (PFS) ratio. First conceived by Daniel Von Hoff more than two decades ago, it is now increasingly being used in precision oncology trials. Here, the PFS ratio is defined as the PFS under a molecularly guided therapy (PFS2) divided by the PFS under the last systemic therapy before molecular tumour profiling (PFS1). A significant therapy response is usually defined as a PFS ratio above 1.3 or 1.5. Methods: To investigate if current PFS ratio cut-offs are in line with the response evaluation by physicians, we conducted a survey among investigators of the MASTER (Molecularly Aided Stratification for Tumor Eradication Research) Program of the German Cancer Consortium. Physicians were asked to classify the success of molecularly guided therapies in 194 patients enrolled in the MOSCATO 01 trial based on PFS1 and PFS2 times. We received 100 complete replies. Results: A comparison of classification profiles revealed three clusters of response assessments. Only one cluster (29% of physicians) was consistent with a PFS ratio cut-off of 1.3, whereas the remaining 71% of participants applied a different classification scheme that did not rely on the relation between PFS times alone, but also took into account absolute PFS1 intervals. Based on these community-driven insights, we developed a modified PFS ratio that factors in the influence of the absolute PFS1 interval. Applying the modified PFS ratio to two recent precision oncology trials, MOSCATO 01 and WINTHER, revealed significantly improved concordance with the physician-perceived clinical benefit, while the proportions of responders to molecularly guided therapies remained largely unchanged. Conclusions: The modified PFS ratio may represent a meaningful clinical endpoint that could aid in the design and interpretation of future precision oncology trials. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.